Various Meanings of Harf Jar Min in Arabic Studies - Muhammad Rinal Saputra; Nur Laila; Shiyam Fajriyanti; Ahmad Hifni (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This article discusses the various interpretations of the harf min in Indonesian by taking a number of examples of verses from the Koran. In the study of Arabic grammar, the harf min is one of the particles that plays a role in changing the final sound of every noun or ism that comes after it, both of nouns in the form of mufrad (singular) and mutsanna (dual) or plural (many). Harfu min is one of the harf jars, while nouns that come after it are called isim majrur. This research is expected to present a comprehensive understanding of the various meanings of harf min. The method used in this research is a qualitative method based on library research. The data sources used are the verses of the Koran, most of which are taken from juz 'amma. This article shows that the harf jar min generally means